Influence of Silage Additives on In Vitro Rumen Fermentation Pattern of Wheat Straw and Green Maize Silage - Belim, Saman Yusufkhan; H. H. Savsani; M. R. Chavda; M. D. Odedra; D. D. Garg; V.K. Karangiya; Y. G. Kansagara (Indian Journal of Animal Nutrition, 2023)
The current investigation was conducted to study various combinations of biological and chemical additives on in vitro rumen fermentation parameters of wheat straw and green maize silage. Different silages were prepared using green maize fodder and wheat straw in the proportion of 10:0 & 7:3 ratio in plastic jar of 3 kg capacity (3 replication in each) by adding common salt @ 0.5%, urea @1% and molasses @ 1.5% in each silages with seven different treatments viz. Control (only green maize), WS (green maize and wheat straw in 7:3 ratio), X (WS added with Xylanase), LP (WS added with  L. plantarum), LF (WS added with L. fermentum), LPLF (WS added with both bacterial inoculants) and XLPLF (WS added with Xylanase and both bacterial inoculants). Xylanase, L. plantarum and L. fermentum were used @ 1500 IU/g, 1 x 106 cfu/g and 2 x 106 cfu/g, respectively. All silages were used for in vitro study after 45 days of ensiling. The result showed that significantly (p